2018
DOI: 10.1021/acs.biochem.8b00960
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin–Ferriprotoporphyrin IX Adduct Abundance in Plasmodium falciparum Malarial Parasites and the Relationship to Emerging Artemisinin Resistance

Abstract: preceding paper in this issue), we quantified free ferriprotoporphyrin IX (FPIX) heme abundance for control versus delayed clearance phenotype (DCP) intraerythrocytic Plasmodium falciparum malarial parasites. Because artemisinin drugs are activated by free FPIX, these data predict that the abundance of long-hypothesized toxic artemisinin drug−FPIX covalent adducts might differ for control versus DCP parasites. If so, this would have important repercussions for understanding the mechanism of the DCP, also known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(62 citation statements)
references
References 62 publications
(128 reference statements)
8
54
0
Order By: Relevance
“…Rab5 proteins have been implicated in hemoglobin import processes, suggesting that the differential associations might impact hemoglobin uptake [63][64][65][66]. These findings recall the recent report of reduced heme and heme-DHA adducts in K13 mutant parasites [29,30]. Birnbaum et al also recently showed reduced endocytosis of host cytoplasm, which consists mainly of hemoglobin, in ring-stage parasites expressing mutant K13 (compared to an isogenic WT control) or WT K13 parasites in which this protein was conditionally knocked sideways to cause loss of function [27].…”
Section: Plos Pathogenssupporting
confidence: 80%
See 1 more Smart Citation
“…Rab5 proteins have been implicated in hemoglobin import processes, suggesting that the differential associations might impact hemoglobin uptake [63][64][65][66]. These findings recall the recent report of reduced heme and heme-DHA adducts in K13 mutant parasites [29,30]. Birnbaum et al also recently showed reduced endocytosis of host cytoplasm, which consists mainly of hemoglobin, in ring-stage parasites expressing mutant K13 (compared to an isogenic WT control) or WT K13 parasites in which this protein was conditionally knocked sideways to cause loss of function [27].…”
Section: Plos Pathogenssupporting
confidence: 80%
“…Mechanistic studies have led to several proposals for how mutant K13 might counter ARTmediated cellular toxicity. These proposals include lowering the levels of the heme activator of ART including via reduced hemoglobin endocytosis in rings [27][28][29][30], upregulating endoplasmic reticulum (ER) stress-response pathways [31], reducing the levels of ubiquitinated proteins [32], promoting translational arrest via differential phosphorylation of the translation initiation factor eIF2α [33], or increasing levels of the phospholipid phosphatidylinositol-3phosphate (PI3P) [34,35]. To gain additional insight into the biology of this protein, we raised K13-specific monoclonal antibodies (mAbs) and used these to interrogate this protein's subcellular localization in DHA-exposed or vehicle-treated asexual blood-stage parasites.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…However, a number of details related to pro drug activation and subsequent target alkylation are yet to be elucidated. For example, the source of Fe 2+ for pro drug activation is not fully defined, although the principle source is likely to be a reduced (ferrous) ferriprotoporphyrin IX (FPIX) heme released during obligate parasite hemoglobin (Hb) catabolism [12].…”
Section: Artemisinins and Actsmentioning
confidence: 99%
“…Artemisinins require activation within cells by scission of an endoperoxide bridge through the Fe 2+ center of heme 1,3 . Cleavage of this bond results in the production of ART radicals, which react with hundreds of proteins 4,5 , lipids 6 , and metabolites, 7 quickly leading to cell death.…”
Section: Introductionmentioning
confidence: 99%